Diaphragm and preparation method and application thereof

By adding specific water-absorbing additives to the coating of the oil-based diaphragm and controlling humidity, the diaphragm electrostatic problem is solved, reducing production costs and improving the performance of the battery cell.

CN119627365APending Publication Date: 2025-03-14ZHEJIANG LIWINON ELECTRONIC TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411607541.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Due to static electricity problems, the existing oil-based diaphragm has complicated process and high cost, and may affect the cycling performance of the battery cell.

Method used

By adding a specific amount and type of water-absorbing additive to the coating of the diaphragm, the ambient humidity is controlled and static electricity is reduced. This method does not require the use of equipment such as electrostatic lamps, electrostatic rods or plasma fans.

Benefits of technology

It effectively reduces the static electricity of the diaphragm, reduces production costs, improves the advantages and overall performance of the battery cell, and reduces the risk of wrinkling on the pole sheet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005130012880000101
    Figure BDA0005130012880000101
  • Figure BDA0005130012880000111
    Figure BDA0005130012880000111
  • Figure BDA0005130012880000121
    Figure BDA0005130012880000121
Patent Text Reader

Abstract

The invention belongs to the technical field of battery materials, and discloses a diaphragm as well as a preparation method and application thereof. The diaphragm comprises a base membrane and a coating on the surface of the base membrane, and the coating comprises PVDF, a ceramic material and a water absorption additive. The coating in the diaphragm contains a specific amount and a specific type of water-absorbing additive, so that the static electricity of the diaphragm is eliminated or reduced. According to the preparation method of the diaphragm, the oil-based diaphragm for eliminating static electricity is prepared by controlling specific environment humidity and adding a specific amount and a specific type of water-absorbing additive. According to the diaphragm for eliminating static electricity, the attraction between the diaphragm and a pole piece caused by static electricity can be reduced, the wrinkling of the pole piece is reduced, and the safety of a battery cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials, and in particular relates to a diaphragm and a preparation method and application thereof. Background Art

[0002] Batteries are widely used, and diaphragms are usually a component of batteries. The performance of diaphragms affects the use of batteries. At present, the mainstream battery diaphragms for 3C products are divided into water-based diaphragms with water as solvent and oil-based diaphragms with polar organic solvents such as NMP (N-methylpyrrolidone). Generally speaking, oil-based diaphragms use PVDF pore-forming materials, so the finished diaphragms have high static electricity problems, which affects the diaphragm coating and battery cell winding process.

[0003] The existing methods to solve the problem of high static electricity in the diaphragm are: ① Adding a static electricity removal lamp, static electricity rod or plasma fan at the tail end of the coating and winding; ② Monitoring the static electricity specifications of incoming materials; ③ Adding a plasma fan at the winding and unwinding end, and a plasma fan at the winding needle end. The above methods increase equipment investment and maintenance costs. In addition, diaphragms with high static electricity will have the risk of wrinkling the pole piece, which will affect the process yield of the battery cell and the later cycle performance, and increase costs.

[0004] Therefore, there is an urgent need to provide a new method for preparing a diaphragm that can eliminate or reduce static electricity, which is conducive to reducing production costs. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a diaphragm and a preparation method and application thereof. The diaphragm preparation method of the present invention does not require the use of an electrostatic lamp, an electrostatic rod or a plasma blower, but controls a specific ambient humidity and adds a specific amount and a specific type of water-absorbing additive to prepare an oil-based diaphragm that eliminates static electricity.

[0006] Since PVDF molecules are a polymer material with extremely high resistivity and contain a large number of highly polar bonds, it is easy for charges to accumulate on its surface. When the oil-based slurry is applied to form a coating, the newly exposed PVDF molecules will gradually accumulate static charges, thereby exhibiting extremely high static electricity. When a specific amount and type of water-absorbing additive is added to the diaphragm coating, a thin layer of water can be formed on the surface of the coating, reducing the resistivity and releasing the charges accumulated by the PVDF, thereby reducing static electricity. After the battery cell is wound or stacked, the excess water can be dried through the conventional baking stage before liquid injection, thereby ensuring that no excess water remains, reducing side reactions of the battery cell, and ensuring the normal use of the battery cell.

[0007] The water-absorbing additive may be an organic material having a large number of hydrophilic groups such as amino, carboxyl, hydroxyl, or a unique three-dimensional spatial network structure and not reacting with the electrolyte, or an inorganic material.

[0008] A first aspect of the present invention provides a diaphragm for eliminating static electricity of an oil-based diaphragm.

[0009] Specifically, a diaphragm for eliminating static electricity of an oil-based diaphragm includes a base film and a coating on the surface of the base film, wherein the coating includes PVDF, a ceramic material and a water-absorbing additive.

[0010] Preferably, the water-absorbing additive does not exceed 5% of the mass of PVDF, for example, 0.001-4.5%.

[0011] Preferably, the water-absorbing additive is a material containing a hydrophilic group or having a three-dimensional network structure.

[0012] Preferably, the hydrophilic group contains one or more of an amino group, a carboxyl group or a hydroxyl group.

[0013] Preferably, the water-absorbing additive includes one or more of starch, cellulose, chitosan, polyamide, polyacrylic acid, polyacrylamide, polyvinyl alcohol, silicate, calcium sulfate, calcium carbonate, and LATP, and polyamide, LATP, and calcium sulfate is more preferred.

[0014] Preferably, the mass ratio of the ceramic material to PVDF is 0.1-11:1, more preferably 0.1-10:1, and even more preferably 1-8:1.

[0015] Preferably, the ceramic material is selected from one or more of silicon carbide ceramics, boron carbide ceramics, titanium carbide ceramics, aluminum oxide ceramics, zirconium oxide ceramics, and beryllium oxide ceramics.

[0016] Preferably, the base film includes any one of a PE (polyethylene) base film, a PP (polypropylene) base film, and a PI (polyimide) base film.

[0017] A second aspect of the present invention provides a method for preparing a membrane.

[0018] Specifically, a method for preparing a diaphragm comprises the following steps:

[0019] (1) Preparation of slurry: PVDF and polar organic solvent are mixed to obtain glue A, and then ceramic material and water-absorbing additive are added to obtain slurry;

[0020] (2) Diaphragm preparation: The slurry is coated on a base film, washed with water, and dried to obtain the diaphragm.

[0021] Preferably, in step (1), PVDF and a polar organic solvent are mixed under the condition that the relative humidity of the environment does not exceed 30% to obtain glue A.

[0022] Preferably, step (1) is carried out under the condition of an ambient relative humidity of 0.01-30%, more preferably under the condition of an ambient relative humidity of 10-30%.

[0023] Preferably, in step (1), the mass ratio of the PVDF to the polar organic solvent is 0.001-1:1, more preferably 0.01-0.8:1, and even more preferably 0.1-0.7:1.

[0024] Preferably, in step (1), the mass ratio of the ceramic material to PVDF is 0.1-11:1, more preferably 0.1-10:1, and even more preferably 1-8:1.

[0025] Preferably, in step (1), the ceramic material is in powder form.

[0026] Preferably, in step (1), the added mass of the water-absorbing additive is 0.001-4.5% of the mass of PVDF, more preferably 0.1-4%, and even more preferably 1-3%.

[0027] Preferably, in step (1), the polar organic solvent includes NMP (N-methylpyrrolidone).

[0028] In step (1), the water absorbing additive is an organic material or an inorganic material that does not react with the electrolyte.

[0029] Preferably, in step (1), the water-absorbing additive contains a large amount of amino groups, carboxyl groups or hydroxyl groups.

[0030] Preferably, in step (2), the slurry is coated on both sides of the base film, and the coating amount on each side is 0.1-0.2 g / m 2 The commonly used total double-sided coating amount is 0.3g / m 2 .

[0031] In step (2), the washing and drying are conventional processes in the art.

[0032] After the diaphragm is dried, a thin water layer can be formed on the coating surface due to the addition of a water-absorbing additive with a certain water-absorbing capacity, which reduces the resistivity and releases the charge accumulated by the PVDF, thereby reducing static electricity. When the battery cell is wound and baked in a vacuum oven, the adsorbed water can be released, thereby ensuring that the water content in the battery cell meets the specification, reducing the reaction between water and electrolyte, and ensuring the normal use of the battery cell.

[0033] A third aspect of the present invention provides use of a separator in a battery.

[0034] A battery comprises the above-mentioned separator.

[0035] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0036] (1) The coating layer in the separator of the present invention contains a specific amount and type of water-absorbing additive to eliminate or reduce the static electricity of the separator.

[0037] (2) The diaphragm preparation method of the present invention does not require the use of an electrostatic lamp, an electrostatic rod or a plasma blower, but instead controls a specific ambient humidity and adds a specific amount and type of water-absorbing additive to prepare an oil-based diaphragm that eliminates static electricity. The diaphragm that eliminates static electricity prepared by the present invention can reduce the attraction between the diaphragm and the electrode due to static electricity, reduce the wrinkling of the electrode, and improve the safety of the battery cell.

[0038] (3) The diaphragm preparation method of the present invention reduces the static electricity of the oil-based diaphragm, reduces the cost and quality rate of the diaphragm manufacturing process, improves the process quality rate of the battery cell winding process, and improves the overall quality rate of the battery cell while ensuring that the performance of the existing oil-based diaphragm remains unchanged.

[0039] (4) The diaphragm preparation method of the present invention can reduce the use of static electricity elimination devices during the preparation process and the use of static electricity elimination devices during the winding process, thereby effectively reducing production costs.

[0040] (5) The anti-static diaphragm prepared by the preparation method of the present invention can effectively reduce the adsorption capacity of suspended matter or foreign matter during use, thereby reducing the accumulation of foreign matter inside the diaphragm, improving the process efficiency of the battery cell and effectively improving the safety performance. DETAILED DESCRIPTION

[0041] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0042] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.

[0043] Example 1: Preparation of diaphragm

[0044] A diaphragm for eliminating static electricity of oil-based diaphragms, comprising a base film (PVDF film) and a coating on the surface of the base film, wherein the coating comprises PVDF, ceramic powder (alumina ceramic) and polyamide, the mass ratio of the ceramic powder (alumina ceramic) to PVDF is 60:40, and the mass of the polyamide is 1% of that of the PVDF.

[0045] A method for preparing an oil-based diaphragm for eliminating static electricity comprises the following steps:

[0046] Preparation of slurry: Under the condition of 30% relative humidity, weigh 10 parts by mass of PVDF and add it to 90 parts by mass of NMP solvent, stir for 12 hours to obtain a transparent solution, which is the initial glue A; take 60 parts by mass of ceramic powder (alumina ceramic) and glue A containing 40 parts by mass of PVDF, stir well for 6 hours, then add 1% of the mass of PVDF polyamide, stir for 6 hours, and finally obtain slurry B;

[0047] Coating the diaphragm: Slurry B is coated on the base film (PVDF membrane), and after washing and drying, the final diaphragm is obtained.

[0048] Coating, washing and drying are conventional processes in this field.

[0049] Example 2: Preparation of diaphragm

[0050] A method for preparing an oil-based diaphragm for eliminating static electricity comprises the following steps:

[0051] Preparation of slurry: Under the condition of 30% relative humidity, weigh 10 parts by mass of PVDF and add it to 90 parts by mass of NMP solvent, stir for 12 hours to obtain a transparent solution, which is the initial glue A; take 60 parts by mass of ceramic powder (alumina ceramic) and glue A containing 40 parts by mass of PVDF, stir well for 6 hours, then add 2% of the mass of PVDF polyamide, stir for 6 hours, and finally obtain slurry B;

[0052] Coating the diaphragm: Slurry B is coated on the base film (PVDF membrane), and after washing and drying, the final diaphragm is obtained.

[0053] Example 3: Preparation of diaphragm

[0054] A method for preparing an oil-based diaphragm for eliminating static electricity comprises the following steps:

[0055] Preparation of slurry: Under the condition of 30% relative humidity, weigh 10 parts by mass of PVDF and add it to 90 parts by mass of NMP solvent, stir for 12 hours to obtain a transparent solution, which is the initial glue A; take 60 parts by mass of ceramic powder (alumina ceramic) and glue A containing 40 parts by mass of PVDF, stir well for 6 hours, then add 3% of the mass of PVDF polyamide, stir for 6 hours, and finally obtain slurry B;

[0056] Coating the diaphragm: Slurry B is coated on the base film (PVDF membrane), and after washing and drying, the final diaphragm is obtained.

[0057] Example 4: Preparation of diaphragm

[0058] A method for preparing an oil-based diaphragm for eliminating static electricity comprises the following steps:

[0059] Preparation of slurry: Under the condition of 30% relative humidity, weigh 10 parts by mass of PVDF and add it to 90 parts by mass of NMP solvent, stir for 12 hours to obtain a transparent solution, which is the initial glue A; take 60 parts by mass of ceramic powder (alumina ceramic) and glue A containing 40 parts by mass of PVDF, stir well for 6 hours, then add 4% of the mass of PVDF polyamide, stir for 6 hours, and finally obtain slurry B;

[0060] Coating the diaphragm: Slurry B is coated on the base film (PVDF membrane), and after washing and drying, the final diaphragm is obtained.

[0061] Example 5: Preparation of diaphragm

[0062] A method for preparing an oil-based diaphragm for eliminating static electricity comprises the following steps:

[0063] Preparation of slurry: Under the condition of 30% relative humidity, weigh 10 parts by mass of PVDF and add it to 90 parts by mass of NMP solvent, stir for 12 hours to obtain a transparent solution, which is the initial glue A; take 60 parts by mass of ceramic powder (alumina ceramic) and glue A containing 40 parts by mass of PVDF, stir well for 6 hours, then add 5% of the mass of PVDF polyamide, stir for 6 hours, and finally obtain slurry B;

[0064] Coating the diaphragm: Slurry B is coated on the base film (PVDF membrane), and after washing and drying, the final diaphragm is obtained.

[0065] Example 6: Preparation of diaphragm

[0066] A method for preparing an oil-based diaphragm for eliminating static electricity comprises the following steps:

[0067] Preparation of slurry: Under the condition of 30% relative humidity, weigh 10 parts by mass of PVDF and add it to 90 parts by mass of NMP solvent, stir for 12 hours to obtain a transparent solution, which is the initial glue A; take 60 parts by mass of ceramic powder (alumina ceramic) and glue A containing 40 parts by mass of PVDF, stir well for 6 hours, then add 1% of the mass of PVDF LATP (lithium oxyphosphosulfate) powder, stir for 6 hours, and finally obtain slurry B;

[0068] Coating the diaphragm: Slurry B is coated on the base film (PVDF membrane), and after washing and drying, the final diaphragm is obtained.

[0069] Example 7: Preparation of diaphragm

[0070] A method for preparing an oil-based diaphragm for eliminating static electricity comprises the following steps:

[0071] Preparation of slurry: Under the condition of 30% relative humidity, weigh 10 parts by mass of PVDF and add it to 90 parts by mass of NMP solvent, stir for 12 hours to obtain a transparent solution, which is the initial glue A; take 60 parts by mass of ceramic powder (alumina ceramic) and glue A containing 40 parts by mass of PVDF, stir well for 6 hours, then add 2% of the mass of PVDF LATP (lithium oxyphosphosulfate) powder, stir for 6 hours, and finally obtain slurry B;

[0072] Coating the diaphragm: Slurry B is coated on the base film (PVDF membrane), and after washing and drying, the final diaphragm is obtained.

[0073] Example 8: Preparation of diaphragm

[0074] A method for preparing an oil-based diaphragm for eliminating static electricity comprises the following steps:

[0075] Preparation of slurry: Under the condition of 30% relative humidity, weigh 10 parts by mass of PVDF and add it to 90 parts by mass of NMP solvent, stir for 12 hours to obtain a transparent solution, which is the initial glue A; take 60 parts by mass of ceramic powder (alumina ceramic) and glue A containing 40 parts by mass of PVDF, stir well for 6 hours, then add 3% of the mass of PVDF LATP (lithium oxyphosphosulfate) powder, stir for 6 hours, and finally obtain slurry B;

[0076] Coating the diaphragm: Slurry B is coated on the base film (PVDF membrane), and after washing and drying, the final diaphragm is obtained.

[0077] Example 9: Preparation of diaphragm

[0078] A method for preparing an oil-based diaphragm for eliminating static electricity comprises the following steps:

[0079] Preparation of slurry: Under the condition of 30% relative humidity, weigh 10 parts by mass of PVDF and add it to 90 parts by mass of NMP solvent, stir for 12 hours to obtain a transparent solution, which is the initial glue A; take 60 parts by mass of ceramic powder (alumina ceramic) and glue A containing 40 parts by mass of PVDF, stir well for 6 hours, then add 4% of the mass of PVDF LATP (lithium oxyphosphosulfate) powder, stir for 6 hours, and finally obtain slurry B;

[0080] Coating the diaphragm: Slurry B is coated on the base film (PVDF membrane), and after washing and drying, the final diaphragm is obtained.

[0081] Example 10: Preparation of diaphragm

[0082] A method for preparing an oil-based diaphragm for eliminating static electricity comprises the following steps:

[0083] Preparation of slurry: Under the condition of 30% relative humidity, weigh 10 parts by mass of PVDF and add it to 90 parts by mass of NMP solvent, stir for 12 hours to obtain a transparent solution, which is the initial glue A; take 60 parts by mass of ceramic powder (alumina ceramic) and glue A containing 40 parts by mass of PVDF, stir well for 6 hours, then add 5% of the mass of PVDF LATP (lithium oxyphosphosulfate) powder, stir for 6 hours, and finally obtain slurry B;

[0084] Coating the diaphragm: Slurry B is coated on the base film (PVDF membrane), and after washing and drying, the final diaphragm is obtained.

[0085] Example 11: Preparation of diaphragm

[0086] A method for preparing an oil-based diaphragm for eliminating static electricity comprises the following steps:

[0087] Preparation of slurry: Under the condition of 30% relative humidity, weigh 10 parts by mass of PVDF and add it to 90 parts by mass of NMP solvent, stir for 12 hours to obtain a transparent solution, which is the initial glue A; take 60 parts by mass of ceramic powder (alumina ceramic) and glue A containing 40 parts by mass of PVDF, stir well for 6 hours, then add 1% calcium sulfate of the mass of PVDF, stir for 6 hours, and finally obtain slurry B;

[0088] Coating the diaphragm: Slurry B is coated on the base film (PVDF membrane), and after washing and drying, the final diaphragm is obtained.

[0089] Example 12: Preparation of diaphragm

[0090] A method for preparing an oil-based diaphragm for eliminating static electricity comprises the following steps:

[0091] Preparation of slurry: Under the condition of 30% relative humidity, weigh 10 parts by mass of PVDF and add it to 90 parts by mass of NMP solvent, stir for 12 hours to obtain a transparent solution, which is the initial glue A; take 60 parts by mass of ceramic powder (alumina ceramic) and glue A containing 40 parts by mass of PVDF, stir well for 6 hours, then add 2% calcium sulfate of the mass of PVDF, stir for 6 hours, and finally obtain slurry B;

[0092] Coating the diaphragm: Slurry B is coated on the base film (PVDF membrane), and after washing and drying, the final diaphragm is obtained.

[0093] Example 13: Preparation of diaphragm

[0094] A method for preparing an oil-based diaphragm for eliminating static electricity comprises the following steps:

[0095] Preparation of slurry: Under the condition of 30% relative humidity, weigh 10 parts by mass of PVDF and add it to 90 parts by mass of NMP solvent, stir for 12 hours to obtain a transparent solution, which is the initial glue A; take 60 parts by mass of ceramic powder (alumina ceramic) and glue A containing 40 parts by mass of PVDF, stir well for 6 hours, then add 3% calcium sulfate of the mass of PVDF, stir for 6 hours, and finally obtain slurry B;

[0096] Coating the diaphragm: Slurry B is coated on the base film (PVDF membrane), and after washing and drying, the final diaphragm is obtained.

[0097] Example 14: Preparation of diaphragm

[0098] A method for preparing an oil-based diaphragm for eliminating static electricity comprises the following steps:

[0099] Preparation of slurry: Under the condition of 30% relative humidity, weigh 10 parts by mass of PVDF and add it to 90 parts by mass of NMP solvent, stir for 12 hours to obtain a transparent solution, which is the initial glue A; take 60 parts by mass of ceramic powder (alumina ceramic) and glue A containing 40 parts by mass of PVDF, stir well for 6 hours, then add 4% calcium sulfate of the mass of PVDF, stir for 6 hours, and finally obtain slurry B;

[0100] Coating the diaphragm: Slurry B is coated on the base film (PVDF membrane), and after washing and drying, the final diaphragm is obtained.

[0101] Example 15: Preparation of diaphragm

[0102] A method for preparing an oil-based diaphragm for eliminating static electricity comprises the following steps:

[0103] Preparation of slurry: Under the condition of 30% relative humidity, weigh 10 parts by mass of PVDF and add it to 90 parts by mass of NMP solvent, stir for 12 hours to obtain a transparent solution, which is the initial glue A; take 60 parts by mass of ceramic powder (alumina ceramic) and glue A containing 40 parts by mass of PVDF, stir well for 6 hours, then add 5% calcium sulfate of the mass of PVDF, stir for 6 hours, and finally obtain slurry B;

[0104] Coating the diaphragm: Slurry B is coated on the base film (PVDF membrane), and after washing and drying, the final diaphragm is obtained.

[0105] Comparative Example 1

[0106] A method for preparing a diaphragm comprises the following steps:

[0107] Preparation of slurry: Under the condition of relative humidity of 30%, 10 parts by mass of PVDF was weighed and added to 90 parts by mass of NMP solvent, and stirred for 12 hours to obtain a transparent solution, which is the initial glue A; 60 parts by mass of ceramic powder (alumina ceramic) and glue A containing 40 parts by mass of PVDF were taken, and stirred for 6 hours to finally obtain slurry B;

[0108] Coating the diaphragm: Slurry B is coated on the base film (PVDF membrane), and after washing and drying, the final diaphragm is obtained.

[0109] Coating, washing and drying are conventional processes in this field.

[0110] Comparative Example 2

[0111] A method for preparing a diaphragm comprises the following steps:

[0112] Preparation of slurry: Under the condition of 50% relative humidity, weigh 10 parts by mass of PVDF and add it to 90 parts by mass of NMP solvent, stir for 12 hours to obtain a transparent solution, which is the initial glue A; take 60 parts by mass of ceramic powder (alumina ceramic) and glue A containing 40 parts by mass of PVDF, stir well for 6 hours, then add 1% of the mass of PVDF polyamide, stir for 6 hours, and finally obtain slurry B;

[0113] Coating the diaphragm: Slurry B is coated on the base film (PVDF membrane), and after washing and drying, the final diaphragm is obtained.

[0114] Comparative Example 3

[0115] A method for preparing a diaphragm comprises the following steps:

[0116] Preparation of slurry: Under the condition of 30% relative humidity, weigh 10 parts by mass of PVDF and add it to 90 parts by mass of NMP solvent, stir for 12 hours to obtain a transparent solution, which is the initial glue A; take 60 parts by mass of ceramic powder (alumina ceramic) and glue A containing 40 parts by mass of PVDF, stir well for 6 hours, then add 10% of the mass of PVDF polyamide, stir for 6 hours, and finally obtain slurry B;

[0117] Coating the diaphragm: Slurry B is coated on the base film (PVDF membrane), and after washing and drying, the final diaphragm is obtained.

[0118] Comparative Example 4

[0119] A method for preparing a diaphragm comprises the following steps:

[0120] Preparation of slurry: Under the condition of 50% relative humidity, weigh 10 parts by mass of PVDF and add it to 90 parts by mass of NMP solvent, stir for 12 hours to obtain a transparent solution, which is the initial glue A; take 60 parts by mass of ceramic powder (alumina ceramic) and glue A containing 40 parts by mass of PVDF, stir well for 6 hours, then add 1% of the mass of PVDF LATP (lithium oxyphosphosulfate) powder, stir for 6 hours, and finally obtain slurry B;

[0121] Coating the diaphragm: Slurry B is coated on the base film (PVDF membrane), and after washing and drying, the final diaphragm is obtained.

[0122] Comparative Example 5

[0123] A method for preparing a diaphragm comprises the following steps:

[0124] Preparation of slurry: Under the condition of 30% relative humidity, weigh 10 parts by mass of PVDF and add it to 90 parts by mass of NMP solvent, stir for 12 hours to obtain a transparent solution, which is the initial glue A; take 60 parts by mass of ceramic powder (alumina ceramic) and glue A containing 40 parts by mass of PVDF, stir well for 6 hours, then add 10% of the mass of PVDF LATP (lithium oxyphosphosulfate) powder, stir for 6 hours, and finally obtain slurry B;

[0125] Coating the diaphragm: Slurry B is coated on the base film (PVDF membrane), and after washing and drying, the final diaphragm is obtained.

[0126] Comparative Example 6

[0127] A method for preparing a diaphragm comprises the following steps:

[0128] Preparation of slurry: Under the condition of 30% relative humidity, weigh 10 parts by mass of PVDF and add it to 90 parts by mass of NMP solvent, stir for 12 hours to obtain a transparent solution, which is the initial glue A; take 60 parts by mass of ceramic powder (alumina ceramic) and glue A containing 40 parts by mass of PVDF, stir well for 6 hours, then add 10% of the mass of PVDF calcium sulfate, stir for 6 hours, and finally obtain slurry B;

[0129] Coating the diaphragm: Slurry B is coated on the base film (PVDF membrane), and after washing and drying, the final diaphragm is obtained.

[0130] Comparative Example 7

[0131] A method for preparing a diaphragm comprises the following steps:

[0132] Preparation of slurry: Under the condition of 30% relative humidity, weigh 10 parts by mass of PVDF and add it to 90 parts by mass of NMP solvent, stir for 12 hours to obtain a transparent solution, which is the initial glue A; take 60 parts by mass of ceramic powder (alumina ceramic) and glue A containing 40 parts by mass of PVDF, stir well for 6 hours, then add 1% boehmite of the mass of PVDF, stir for 6 hours, and finally obtain slurry B;

[0133] Coating the diaphragm: Slurry B is coated on the base film (PVDF membrane), and after washing and drying, the final diaphragm is obtained.

[0134] Product effect testing

[0135] The diaphragms prepared in the above embodiments and comparative examples were tested for diaphragm static electricity, winding quality, and battery cell water content. The specific test method is as follows, and the test results are shown in Table 1.

[0136] Diaphragm electrostatic test: refer to GB / T14447-1993 "Plastic Film Electrostatic Test Method Half-Life Method", under the specified test conditions, apply high voltage to the discharge electrode, charge the sample in the form of corona discharge, after stopping the application of high voltage, the sample is grounded and decays naturally, test the half-life of the sample to evaluate the charge leakage performance of the sample after being charged, and the electrostatic value ≤800V is qualified.

[0137] Winding quality rate: The ratio of the total number of wound cells minus the number of defective cells in the winding process to the total number of cells. The winding quality rate ≥ 90% is qualified.

[0138] Cell water content: Before filling the cell with liquid, bake the cell at 80℃ in vacuum for 48 hours, and cut off about 1-2g of the bare cell corner. Use Karl Fischer solid moisture meter to measure the cell water content, test conditions 150℃, 5min. The cell water content ≤90ppm is qualified.

[0139] Table 1: Surface component characteristics of base film in Examples and Comparative Examples

[0140]

[0141]

[0142]

[0143] The calcium sulfate and LATP contain three-dimensional network structures, and the surface of the polyamide contains hydrophilic groups.

[0144] Except for Comparative Examples 2 and 4 in which the separators were prepared under the condition of an ambient relative humidity of 50%, the separators in other Examples and Comparative Examples were prepared under the condition of an ambient relative humidity of 30%.

[0145] Table 2: Performance test results

[0146]

[0147]

[0148] The water-absorbing additive used in Examples 1-5 is polyamide, and the content of polyamide increases from 1% to 5% of the mass of PVDF. The water-absorbing additive used in Examples 6-10 is LATP (lithium oxyphosphosulfate) powder, and the content of LATP (lithium oxyphosphosulfate) powder increases from 1% to 5% of the mass of PVDF. The water-absorbing additive used in Examples 11-15 is calcium sulfate, and the content of calcium sulfate increases from 1% to 5% of the mass of PVDF. Comparative Example 1 does not use a water-absorbing additive. Although Comparative Examples 2 and 4 both use a water-absorbing additive, the slurry is prepared under the condition of an ambient relative humidity of 50%. The mass of polyamide in Comparative Example 3 is 10% of the mass of PVDF, the mass of LATP (lithium oxyphosphosulfate) powder in Comparative Example 5 is 10% of the mass of PVDF, and the mass of calcium sulfate in Comparative Example 6 is 10% of the mass of PVDF.

[0149] As can be seen from Table 1, in the process of preparing the diaphragm, when the content of the water-absorbing additive is too high (Comparative Example 2, Comparative Example 4, Comparative Example 6), the water content of the battery cell will be too high. When the water-absorbing additive is not used (such as Comparative Example 1), the static electricity of the prepared diaphragm is too large, which affects the winding quality rate and does not meet the standard.

[0150] It can be seen from Examples 1-5, 6-10, and 11-15 that when the water-absorbing additive used is LATP (lithium oxyphosphate sulfate) powder, the effect of the diaphragm in eliminating static electricity is better than that of polyamide and calcium sulfate. The higher the content of the water-absorbing additive, the better the effect of the diaphragm in eliminating static electricity, but the water content of the battery cell will increase. It can be seen that the type and content of the water-absorbing additive have an impact on the effect of eliminating static electricity of the diaphragm.

[0151] It can be seen from Comparative Example 7 and Example 11 that when the added water-absorbing additive does not have a three-dimensional network structure, although the water content of the battery cell is qualified, the water absorption capacity decreases, the static electricity of the separator is large, and the winding rate of the battery cell is unqualified. It can be seen that whether the water-absorbing material has a three-dimensional network structure has an impact on the anti-static effect of the separator.

Claims

1. A diaphragm, characterized in that: The invention comprises a base film and a coating on the surface of the base film, wherein the coating comprises PVDF, a ceramic material and a water-absorbing additive.

2. The diaphragm according to claim 1, characterized in that The water-absorbing additive is a material containing a hydrophilic group or having a three-dimensional network structure.

3. The diaphragm according to claim 2, characterized in that The hydrophilic group contains one or more of amino, carboxyl or hydroxyl groups.

4. The diaphragm according to claim 1, characterized in that The water-absorbing additive includes one or more of starch, cellulose, chitosan, polyamide, polyacrylic acid, polyacrylamide, polyvinyl alcohol, silicate, calcium sulfate, calcium carbonate, and LATP, preferably one or more of polyamide, LATP, and calcium sulfate.

5. The diaphragm according to claim 1, characterized in that The amount of the water absorbing additive does not exceed 5% of the mass of PVDF.

6. The diaphragm according to claim 1, characterized in that The mass ratio of the ceramic material to PVDF is 0.1-11:1; and / or the ceramic material is selected from one or more of silicon carbide, boron carbide, titanium carbide, aluminum oxide, zirconium oxide, and beryllium oxide.

7. The diaphragm according to claim 1, characterized in that The base film includes any one of a PE base film, a PP base film, and a PI base film.

8. The method for preparing a diaphragm according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Preparation of slurry: PVDF and polar organic solvent are mixed to obtain glue A, and then ceramic material and water-absorbing additive are added to obtain slurry; (2) Diaphragm preparation: The slurry is coated on a base film, washed with water, and dried to obtain the diaphragm.

9. The preparation method according to claim 8, characterized in that: In step (1), PVDF and a polar organic solvent are mixed under the condition that the relative humidity of the environment does not exceed 30% to obtain glue A.

10. A battery, characterized in that: The invention comprises the diaphragm according to any one of claims 1 to 7.